Forming Connections between Security Sector Reform and Sustainable Development: The Potential of the Human Security Paradigm - Dursun-Özkanca, Oya; Glušac, Luka (Journal of Regional Security, 2024)
Many interlinkages already exist between security and development, despite the fact they traditionally maintained separate bodies of literature and compartmentalized presence in policymaking. This article seeks to provide guidance on how to bridge the gap between the two. It focuses on the nexus between Security Sector Reform (SSR) and Sustainable Development Goals, particularly SDG-16 devoted to effective, accountable and inclusive institutions. It argues that the human security paradigm provides the most rewarding approach for bridging the gap between these two, as it centres the focus on the human element of these two endeavours. It first provides an overview of the security-development nexus, followed by a discussion of the commonalities and differences between SSR and SDG-16 specifically, outlining how human security provides a better connection between the two. It concludes that the bottom-up and multistakeholder approaches of the human security paradigm and its context-specific perspective ensure that the SSR missions and attainment of the SDG-16 targets will be more effective and efficient.